Identification of Landfill Using Refraction Seismic Method in LIPI Area - Bandung - Resi Wasilatus Syifa; Nur Ichsan Sumardani; Nur Amalia Dewi; Teti Febrianti; Jauhari Arifin; Bebeh Wahid Nuryadin (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2020)
Research has been carried out using seismic refraction in the LIPI area - Bandung, which aims to determine the land of embankment in the area. Retrieval of field data was carried out using geometric Es-3000 tool along 46 meters with a spacing of 2 meters and a 7 shoot punch consisting of 2 phantom shoots beginning and ending. Data processing is done by the first step, namely by geometric editing so that data can be read by the computer. The inversion process is done by seismimager software which consists of pickwin to extract data and plotera for modeling the subsurface layer. The results of the data interpretation show the P wave velocity from 315 - 435 m / s. layer grouping based on P wave velocity is at the first color layer having a wave velocity of about 315 - 342 m / s, the second color layer has a wave speed of 355-382 m / s, and the third color layer has a speed of 359 - 422 m / s and thick layer more than 435. Based on the lithological classification of subsurface rock layers, this study area tends to have a layer of soil type with a depth of 5 meters, and can be said to be a layer of soil deposits because of the formation of soil structures that tend to be new